Molecular Basis of N,N-Diethyl-3-Methylbenzamide (DEET) in Repelling the Common Bed Bug, Cimex lectularius - Liu, Feng; Xia, Xiaoming; Liu, Nannan (Frontiers in Physiology, 2017)
As the most extensively used chemical repellent, N,N-diethyl-3-methylbenzamide (DEET) displayed repellency to a wide range of insects, including the common bed bug, Cimex lectularius. While the neuronal or molecular basis involved in DEET’s repellency have been majorly focused on mosquitos and fruit flies, DEET’s repellency to the common bed bug is largely unreached. To gain new insights into the cellular and molecular mechanisms in DEET’s repellency to the common bed bug, we characterized the neuronal response of bed bugs to DEET, identified the olfactory receptors targeted by DEET and demonstrated the interfering effect of DEET on bed bug’s responses to human odorants. High doses of DEET were required for activating the olfactory receptor neurons in the sensilla of bed bugs and at least three DEET-sensitive receptors were functionally deciphered. These DEET-sensitive receptors presented even more sensitive to certain botanical terpenes/terpenoids which also displayed repellency at varying levels for bed bugs. In addition, DEET produced a blocking effect on the neuronal responses of bed bugs to specific human odors and showed inhibitory effect on the function of odorant receptors in responding to certain human odors. Taken together, our results indicate that DEET functions as a stimulus that triggered avoidance behaviors and a molecular ‘confusant’ for interrupting the host odor recognition in the odorant receptors of bed bugs. The receptors that coincidently responded to both synthetic DEET and botanical terpenes/terpenoids suggested that DEET may target on receptors that originally responded to terpenes/terpenoids. This study gave novel insights into the mechanisms of DEET’s repellency to bed bugs and also provided valuable information for developing new reagents for bed bug control.